2019
DOI: 10.1016/s1473-3099(19)30266-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of an anti-Middle East respiratory syndrome coronavirus DNA vaccine: a phase 1, open-label, single-arm, dose-escalation trial

Abstract: Background Middle East respiratory syndrome (MERS) coronavirus causes a highly fatal lower-respiratory tract infection. There are as yet no licensed MERS vaccines or therapeutics. This study (WRAIR-2274) assessed the safety, tolerability, and immunogenicity of the GLS-5300 MERS coronavirus DNA vaccine in healthy adults. Methods This study was a phase 1, open-label, single-arm, dose-escalation study of GLS-5300 done at the Walter ReedArmy Institute for Research Clinical Trials Center (Silver Spring, MD, USA). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
288
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(306 citation statements)
references
References 22 publications
4
288
0
5
Order By: Relevance
“…Most studies on SARS and MERS vaccines were excluded as they were performed in cell or animal models ( Figure 1). The four studies included in this review were Phase I clinical trials on SARS or MERS vaccines (Table 4) [44][45][46][47]. There were no studies of any population type (cell, animal, human) on the 2019-nCoV at the point of screening.…”
Section: Potential Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on SARS and MERS vaccines were excluded as they were performed in cell or animal models ( Figure 1). The four studies included in this review were Phase I clinical trials on SARS or MERS vaccines (Table 4) [44][45][46][47]. There were no studies of any population type (cell, animal, human) on the 2019-nCoV at the point of screening.…”
Section: Potential Vaccinesmentioning
confidence: 99%
“…The latest findings for these vaccines arebased on the review by Yong et al (2019) in August 2019 [110]. As of the date of reporting, there is only one published clinical study on the MERS-CoV vaccine by GeneOne Life Science & Inovio Pharmaceuticals [47]. There was one SARS vaccine trial conducted by the US National Institute of Allergy and Infectious Diseases.…”
Section: Vaccinesmentioning
confidence: 99%
“…Most of them have been tested in mouse models and showed the ability to elicit neutralizing antibodies. The first SARS-CoV DNA vaccine was tested in humans only 19 months after the virus sequence was published [38], while the DNA vaccine GLS-5300, the first MERS-CoV vaccine, went to clinical trials in 2016 [39]. In addition to these conventional vaccines, Liu et al analyzed the T cell epitopes of SARS-CoV and MERS-CoV, revealed the potential cross-reactivity of the coronaviruses, and assessed the possibility of developing universal vaccines against coronavirus infections [40].…”
Section: Research and Development Of Vaccinesmentioning
confidence: 99%
“…Seroconversion was detected in 95% of patients. MERS-CoV-specific T cell responses were detected in 76% of patients and persisted at 60 days post-final immunization [19 ].…”
Section: Current Opinion In Immunologymentioning
confidence: 99%